Spillover of Ratings of Patient- and Family-Centered Care. Issue 4 (October 2016) - Christensen, Anna L.; Brown, Jonathan D.; Wissow, Lawrence S.; Cook, Benjamin
Abstract : As primary care models increasingly include nonphysician team members, more attention should be paid to patient- and family-centered care (PFCC) among medical assistants (MAs). The aims of this article are to describe parent perceptions of PFCC by MAs and assess associations between MA PFCC and other perceptions of their care experience. To assess PFCC, we administered the CARE (Consultation and Relational Empathy) measure to the parent/guardian of 360 children following a primary care visit. Perceptions of PFCC by MAs were significantly associated with 6 of 7 other measures of patient experience, including PFCC by the physician, treatment by the receptionist, and satisfaction with wait time. Each team member can potentially shape perceptions of care in ways that could "spill over" into other parts of the visit.